Genetic variants in five novel loci including CFB and CD40 predispose to chronic hepatitis B. Issue 1 (28th April 2015) - Jiang, De‐Ke; Ma, Xiao‐Pin; Yu, Hongjie; Cao, Guangwen; Ding, Dong‐Lin; Chen, Haitao; Huang, Hui‐Xing; Gao, Yu‐Zhen; Wu, Xiao‐Pan; Long, Xi‐Dai; Zhang, Hongxing; Zhang, Youjie; et al.
Abstract : Hepatitis B virus affects more than 2 billion people worldwide, 350 million of which have developed chronic hepatitis B (CHB). The genetic factors that confer CHB risk are still largely unknown. We sought to identify genetic variants for CHB susceptibility in the Chinese population. We undertook a genome‐wide association study (GWAS) in 2, 514 CHB cases and 1, 130 normal controls from eastern China. We replicated 33 of the most promising signals and eight previously reported CHB risk loci through a two‐stage validation totaling 6, 600 CHB cases and 8, 127 controls in four independent populations, of which two populations were recruited from eastern China, one from northern China and one from southern China. The joint analyses of 9, 114 CHB cases and 9, 257 controls revealed significant association of CHB risk with five novel loci. Four loci are located in the human leukocyte antigen (HLA) region at 6p21.3, including two nonsynonymous variants (rs12614 [R32W] in complement factor B [ CFB ], P meta =1.28 × 10 −34 ; and rs422951 [T320A] in NOTCH4, P meta = 5.33 × 10 −16 ); one synonymous variant (rs378352 in HLA‐DOA corresponding to HLA‐DOA *010101, P meta = 1.04 × 10 −23 ); and one noncoding variant (rs2853953 near HLA‐C, P meta = 5.06 × 10 −20 ). Another locus is located at 20q13.1 (rs1883832 in the Kozak sequence of CD40, P meta = 2.95 × 10 −15 ). Additionally, we validated seven of eight previously reported CHB susceptibility loci (rs3130542 at HLA‐C, rs1419881 at TCF19, rs652888 at EHMT2, rs2856718 at HLA‐DQB1, rs7453920 at HLA‐DQB2, rs3077 at HLA‐DPA1, and rs9277535 at HLA‐DPA2, which are all located in the HLA region, 9.84 × 10 −71 ≤ P meta ≤ 9.92 × 10 −7 ). Conclusion : Our GWAS identified five novel susceptibility loci for CHB. These findings improve the understanding of CHB etiology and may provide new targets for prevention and treatment of this disease. (Hepatology 2015;62:118‐128)